Pengaruh Supervisor Support Terhadap Turnover Intention Yang Di Mediasi Oleh Employee Engagement Pada Perusahaan Manufaktur Di Kawasan EJIP - Patricia Putri Wulandari; Muhamad Ekhsan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The study looks at how senior support affects the number of employees leaving a manufacturing company in the EJIP area, which is an integrated manufacturing industrial area in Cikarang, Bekasi. The study includes 77 workers from manufacturing companies, which is mostly made up of manufacturing plants from different sectors. One of the factors that may influence employees to leave the company is the lack or excess of superior support and the level of employee involvement that is minimal or overrepresented. Research shows that employee resilience has a significant positive impact on exit intensity. This finding also shows that superior support can also contribute to employee engagement. In addition, senior support also has a positive effect on employee exit intensity due to the presence of inappropriate senior support, resulting in an increase in employees who intend to exit the company. As well, employee involvement can contribute as a mediator between turnover intentions and supervisory support. The study's limitations include a limited number of respondents and a single study location. Therefore, we recommend expanding the sample from multiple companies, incorporating additional independent variables, employing diverse data collection methods, and conducting longitudinal research to observe changes in the phenomenon over time.